Basic Principles of Intraoperative Ultrasound Applied to Brain Tumor Surgery - Javier A. Jacobo; Javier Avendaño; Sergio Moreno-Jimenez; Santiago Nuñez; Rocio Mamani (Indian Journal of Neurosurgery)
Intraoperative ultrasound (US) has been shown to possess great value in assessing tumor volume and localization, especially for primary resection of gliomas and metastatic lesions. Given that US is a technology that is highly user dependent, many surgeons have encountered problems with the usage of this technology, as well as interpretation of intraoperative US images, limiting its full potential. This article focuses on the basic knowledge a neurosurgeon must acquire to properly use and interpret intraoperative US to improve tumor localization and extent of resection during brain tumor surgery.